2020
DOI: 10.1002/elan.202060409
|View full text |Cite
|
Sign up to set email alerts
|

Activated Carbon Derived from Rice Husk as Efficient Oxygen Reduction Catalyst in Microbial Fuel Cell

Abstract: In microbial fuel cells (MFCs), an important factor limiting practical applications is the high catalyst cost in cathode. Herein a rice husk-based porous carbon made through hydrolysis, activation and rolling was used as novel cathode. These porous carbons were characterized by SEM, XPS and BET analysis, and electrochemical measurements including linear sweep voltammetry and Tafel test were investigated. A maximum powder density (317.7 � 0.4 mW m À 2) on AC-KOH-1h with the largest BET surface area of 1809 m 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…This indicated the incorporation of B moieties within the skeletons via the formation of B−C and B−N bonds, which was further verified by the N1s XPS, which was composed of two peaks with BE of 398.2 (B−N) and 399.3 eV (C−N) [31] . Correspondingly, the carbon species existed in the form of C−B (283.6 eV), C−C/C−H (284.4 eV), C−N (287.0 eV) [62–66] . Inductively Coupled Plasma Optical Emission Spectrometry (ICP‐OES) analysis revealed that no detectable Ni (<0.0009 ppm) was observed in the as‐produced BN‐NCN‐T ( T =550, 650, 750, and 850) catalysts.…”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…This indicated the incorporation of B moieties within the skeletons via the formation of B−C and B−N bonds, which was further verified by the N1s XPS, which was composed of two peaks with BE of 398.2 (B−N) and 399.3 eV (C−N) [31] . Correspondingly, the carbon species existed in the form of C−B (283.6 eV), C−C/C−H (284.4 eV), C−N (287.0 eV) [62–66] . Inductively Coupled Plasma Optical Emission Spectrometry (ICP‐OES) analysis revealed that no detectable Ni (<0.0009 ppm) was observed in the as‐produced BN‐NCN‐T ( T =550, 650, 750, and 850) catalysts.…”
Section: Resultsmentioning
confidence: 69%
“…[31] Correspondingly, the carbon species existed in the form of CÀ B (283.6 eV), CÀ C/CÀ H (284.4 eV), CÀ N (287.0 eV). [62][63][64][65][66] Inductively Coupled Plasma Optical Emission Spectrometry (ICP-OES) analysis revealed that no detectable Ni (< 0.0009 ppm) was observed in the as-produced BN-NCN-T (T = 550, 650, 750, and 850) catalysts.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the higher level of i 0 showed more efficient electronic utilization and a quicker reaction rate. 53 The main differences in the Tafel curves for all catalysts appeared at an overpotential above 50 mV. Meanwhile, the Fe–Cu–NC-50% catalyst exhibited a higher value of the curve than other catalysts at an overpotential above 50 mV.…”
Section: Resultsmentioning
confidence: 88%
“…RH charcoal was also used as anode and cathode electrodes for MFC, showing the potential of RH to be used not only as a carbon source for microbes but also in the construction of MFC [192]. Jiao et al [193] indicated that the power density is influenced by the surface area of the carbon electrode, i.e. porosity, used in MFC.…”
Section: Cbp For Bioethanolmentioning
confidence: 99%